Mapping Research on PPE Use and Risk Perception in the Maritime Industry: A Bibliometric Approach - Chairiyanti Chairiyanti; Adi Nugroho; Silvia Kristanti Tri Febriana; Nelly Al Audhah; Meitria Syahadatina Noor (Universitas Malahayati Lampung, 2025)
ABSTRACT Occupational safety in the maritime industry relies heavily on the use of Personal Protective Equipment (PPE) and the understanding of risk perception by ship crews. Despite this, there is still a gap in a comprehensive understanding of research patterns and developments in this area. This study aims to map and analyze research trends related to the use of PPE and risk perception in the maritime industry using a bibliometric approach. The research method used the Publish or Perish application to identify 50 relevant articles from the period 2014-2024, which were then analyzed using VOSviewer with the application of occurance 4 and term 23 criteria to produce network, overlay, and density visualizations. The results showed the dominance of Scandinavian countries in publications, with Sweden (9 publications) and Norway (7 publications) as the main contributors. Analysis of publication types showed a predominance of empirical research articles (34 publications), with peak productivity in 2018. VOSviewer identified three main clusters of research: operational aspects of PPE, regulation and compliance, and analysis and evaluation. The highest keyword frequencies were found in